Modeling of Traffic Flow Schemes at Road Intersections in Pekanbaru City Using Compatible Graphs - Sarbaini Sarbaini (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2022)
Congestion is one of the few issues that has always been the center of attention at crossroads. One of them is at the intersection of Tuanku Tambusai, Nangka and Soekarno Hatta road. This congestion can be reduced by optimizing the duration of pauses at road intersections and collecting a compatible traffic flow when a red light occurs. The two traffic flows are said to be compatible if the two flows are running together without anyone crashing. A compatible graph is a graph that has two sets in which the object to be arranged is indicated by its points, and the corresponding pair of objects is indicated by its sides. This study obtained the optimal pause duration, which assumes a left turn following a red light for 75 seconds, by applying a compatible graph. Furthermore, the optimal duration of the pause assumes that the left turn does not follow the red light for 45 seconds. The pause duration is smaller than the duration now used on Soekarno Hatta Road, which is 115 seconds, using the assumption of following the red light to turn left. So obtained, the duration of the pause is much more optimal when compared to the duration of the pause used on the current Soekarno Hatta road